Older adults’ perceptions of online physical exercise management - Peterlin, Judita; Dimovski, Vlado; Colnar, Simon; Blažica, Bojan; Kejžar, Anamarija (Frontiers in Public Health, 2024)
The study addresses the challenges of digitally transforming physical exercises for older adults (aged more than 55 years) to be performed in virtual environments (during the COVID-19 pandemic) as a long-term proactive strategic initiative in response to the global ageing society and technological development trend. A focus group with a sample of 24 older adults and three trainers were used as part of a 3-month physical exercise pilot conducted by the Jožef Stefan Institute to identify the skills and well-being gained and identify factors that influence success with online exercises for older adults on the individual and organisational levels. First, on the individual level, communication differences were identified when comparing face-to-face exercises with online exercises. Second, on the organisational level, the study identified several challenges arising from the digital transformation of exercises (i.e., onboarding, technical, structural, isolation and motivational). Finally, recommendations are proposed to transform older adults’ exercises when performed in a virtual environment. The study results can also benefit health management practices and theory in the work environment to ensure that older workers can still utilise their strengths to perform successfully while remaining healthy. Online physical exercises tailored to older adults’ needs and specifications could be provided as part of corporate wellness programmes in organisations.